VARIOUS ENGLISH EQUIVALENTS OF INDONESIAN PREPOSITION 'PADA' IN 'LASKAR PELANGI' NOVEL TRANSLATION - Afrianto Afrianto; Ummiatun Ma'rifah (Leksema: Jurnal Bahasa dan Sastra, 2020)
This research was aimed at finding out the English equivalent for Indonesian preposition pada and classifying its function based on Quirk’s framework. By using descriptive-qualitative approach, this research administered documentary search to gather the data. The data were in the form of sentences containing preposition pada and its equivalents taken from a pair of and novels entitled LaskarPelangi (Indonesian) and The Rainbow Troops (English). From this research,  it was revealed that the preposition ‘pada’ can be translated into various English equivalents. There are thirteen equivalents found in the form of preposition and one to infinitive verb. In addition, the preposition ‘pada’ has four functions which become the classification for the equivalents found, mnamely marker of place (on, for, to, at, and in), marker of time (on, in, at, within, and during), marker of recipient (to, for, of, with, around, throughout, about, at, and on), and marker of cause (with, by, and to face). In closing, this research posited that to determine the best English equivalent for pada, it is necessary to pay attention to the grammatical matters and the context of the sentence.